Technically approaching the semantic web bottleneck. (23rd August 2010) - Konstantinou, Nikolaos; Spanos, Dimitrios-Emmanuel; Stavrou, Periklis; Mitrou, Nikolas
After several years of research, the fundamental semantic web technologies have reached a high maturity level. Nevertheless, the average web user has not yet taken advantage of their full potential. In this paper, we introduce the semantic web bottleneck, analyse the main problems that preserve it and suggest ways to overcome it. In particular, we discuss the issues involved in deploying, maintaining and using semantically rich web applications, decomposing this process into two primal ones: publishing and exploiting semantic content. We analyse the role of key players such as the web industry, the search engines, the academia, the web user, and the web engineers that essentially materialise and use these technologies. A roadmap is provided in order for the semantic web to gain further acceptance, based on three major axes: simplicity, mainly entailed by automation, integration with the existing technologies and practices, and adoption by the web industry driving forces.